Change processes in psychotherapy for patients presenting with histrionic personality disorder. (6th July 2022) - Babl, Anna; Gómez Penedo, Juan Martín; Berger, Thomas; Schneider, Noemi; Sachse, Rainer; Kramer, Ueli
Abstract: Objective: Histrionic personality disorder (HPD) with a lifetime prevalence rate of 1.8% is an under‐researched psychiatric diagnosis. The present study therefore aimed to investigate both the processes and outcomes of psychotherapy for HPD in a non‐controlled study. Methods: A total of 159 patients diagnosed with HPD were recruited and received clarification‐oriented psychotherapy. Sessions 15, 20, and 25 were video‐recorded and analysed using the Process‐Content‐Relationship Scale. Therapy outcome was assessed with symptom measures at intake and discharge. Hierarchical linear modelling was applied to estimate the changes in the psychotherapeutic outcome and associations with patient and therapist process developments. Results: Improvements in relationship processes of patients and therapists were systematically related to outcome while only partial relationships were found on the levels of process and content. Conclusion: The present study represents the first systematic insight into core changes in patients with HPD undergoing psychotherapy.